The distinction and intersection of legacies: structural links and differences between Benjamin de Oliveira and Chiquinha Gonzaga - Rocha, Maristela (Comparative Cultural Studies: European and Latin American Perspectives, 2023)
The last decades of the Nineteenth Century are relevant for the history of the Brazilian music, considering that in this period the European influences began to have an impact on the emerging urban culture, a process that would be consolidated throughout the Twentieth Century. Various artists with multiple abilities were in vogue at that time such as the composer, singer, instrumentalist, actor, director, and clown from Minas Gerais state, Benjamin de Oliveira (1870-1954) whose contribution to the process of insertion of the circus-theater in the frame of the Brazilian culture is a fact of great magnitude that worthies being revived, especially after its 150th anniversary. Another personality this article focus on is the pianist, composer and conductor Chiquinha Gonzaga (1847-1935), a pioneer in many segments of the Brazilian culture. She was an outstanding female figure whose contribution has not yet been recognized accordingly by most of the Brazilian people. The approach on the work of these two artists will be made taking into account some bibliographical data, documents from research, structural issues, distinctions and intersections involving the productions of these two great artists who lived in the first days of post-colonial Brazil, a time when the European influence was still very strong among us. Finally, we shall use some advertisements and newspapers excerpt, scanned throughout the text, in order to endorse our conjectures.